Integrating Local Wisdom into Natural Resource Management: A Case Study of Sabah, Malaysia : Mengintegrasikan Kearifan Lokal ke dalam Pengelolaan Sumber Daya Alam: Studi Kasus Sabah, Malaysia - Andy Russel Mojiol (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Natural resource management is increasingly recognized as a critical component of sustainable development, particularly when informed by local wisdom. This paper explores the integration of indigenous knowledge systems in Sabah, Malaysia, focusing on how traditional practices contribute to effective environmental stewardship. Drawing from field observations and documented practices, including the Tagal system of the Kadazan-Dusun community, community-based mangrove tourism, and ethnobotanical knowledge, this study highlights the significance of local wisdom in fostering ecological balance and sustainability. Local wisdom encompasses a range of practices and beliefs passed down through generations, emphasizing harmony with nature and communal resource management. The findings suggest that incorporating these traditional approaches into formal Sustainable Forest Management (SFM) frameworks can enhance biodiversity conservation, promote community resilience, and ensure equitable benefits. This study advocates for policies that formally recognize and empower local communities, ensuring their knowledge and voices are integral to decision-making processes for natural resource management in Sabah, Malaysia and similar regional contexts.